PIJAT PERUT MENURUNKAN TINGKAT KONSTIPASI PADA LANJUT USIA - Erna Dwi Wahyuni; Silvia Lusiana Suwandi; Setho Hadisuyatmana (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Constipation is one of the results of decreased body structure and function in the elderly. One way that can be used to prevent constipation is by doing abdominal massage. The purpose of this research was to determine the influence of abdominal massage on prevention of constipation for elderly. Method: This research used Quasy experiment method by using pre-test-post-test with control group design. The study population was elderly at the nursing home which had risk of constipation amounted to 38 respondents. The sample was 30 respondents with sample random sampling technique. Independentvariables were abdominal massage and the dependent variable was constipation level. Data were collected using Constipation Assessment Scale. Data were analyzed using the Wilcoxon sign rank test and Mann-Whitney test.Result: The results showed statistic test using Wilcoxon in the treatment group showed there was a decrease of constipation level before and after receiving an abdominal massage, with p-value = 0.001 and in the control group there was no difference of constipation level with p-value = 0.057. The results of MannWhitney, showed a difference in abdominal massages to prevent constipation in the elderly with a value of p = 0.033.Discussion: Stimulation from the outside with abdominal massage can help stimulate the parasympathetic nerve in the intestine and accelerate blood circulation, so that weakened bowel peristaltic becomes increased. In this study, abdominal massage was statistically significant against the prevention of constipation in the elderly but clinicallynot too significant.